Double heterozygous mutations of MITF and PAX3 result in Waardenburg syndrome with increased penetrance in pigmentary defects. (19th April 2013) - Yang, T; Li, X; Huang, Q; Li, L; Chai, Y; Sun, L; Wang, X; Zhu, Y; Wang, Z; Huang, Z; Li, Y; Wu, H
Abstract : Yang T, Li X, Huang Q, Li L, Chai Y, Sun L, Wang X, Zhu Y, Wang Z, Huang Z, Li Y, Wu H. Double heterozygous mutations of MITF and PAX3 result in Waardenburg syndrome with increased penetrance in pigmentary defects. Waardenburg syndrome (WS) is characterized by sensorineural hearing loss and pigmentary defects of the hair, skin, and iris. Heterozygous mutations of MITF and its transactivator gene PAX3 are associated with Waardenburg syndrome type II (WS2) and type I (WS1), respectively. Most patients with MITF or PAX3 mutations, however, show variable penetrance of WS‐associated phenotypes even within families segregating the same mutation, possibly mediated by genetic background or specific modifiers. In this study, we reported a rare Waardenburg syndrome simplex family in which a pair of WS parents gave birth to a child with double heterozygous mutations of MITF and PAX3 . Compared to his parents who carried a single mutation in either MITF or PAX3, this child showed increased penetrance of pigmentary defects including white forelock, white eyebrows and eyelashes, and patchy facial depigmentation. This observation suggested that the expression level of MITF is closely correlated to the penetrance of WS, and variants in transcription regulator genes of MITF may modify the relevant clinical phenotypes.